British Association of Dermatologists guidelines for the management of lichen sclerosus, 2018. (18th April 2018) - Lewis, F.M.; Tatnall, F.M.; Velangi, S.S.; Bunker, C.B.; Kumar, A.; Brackenbury, F.; Mohd Mustapa, M.F.; Exton, L.S.
Abstract : Linked Comment: Akel and Fuller. Br J Dermatol 2018; 178 :823–824 . Plain language summary available online